2014
DOI: 10.3389/fpls.2014.00486
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and functional analysis of CONSTANS-LIKE genes suggests that a central role for CONSTANS in flowering time control is not evolutionarily conserved in Medicago truncatula

Abstract: The zinc finger transcription factor CONSTANS has a well-established central role in the mechanism for photoperiod sensing in Arabidopsis, integrating light and circadian clock signals to upregulate the florigen gene FT under long-day but not short-day conditions. Although CONSTANS-LIKE (COL) genes in other species have also been shown to regulate flowering time, it is not clear how widely this central role in photoperiod sensing is conserved. Legumes are a major plant group and various legume species show sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
105
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(115 citation statements)
references
References 63 publications
6
105
0
Order By: Relevance
“…In both monocots and dicots the COL (CONSTANS-Like) family has many members such as 17 in Arabidopsis, 16 in rice, 9 in barley (Griffiths et al 2003), 10 in sugarbeet (Chia et al 2008), 11 in Medicago (Wong et al 2014), 26 in soybean (Wu et al 2014) and 23 in cotton (Zhang et al 2015). All of these COL genes are characterized by the presence of three domains namely the B-box 1, B-box 2 and a CCT (CO, COlike, and TOC1) domain (Griffiths et al 2003;Putterill et al 1995;Strayer et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In both monocots and dicots the COL (CONSTANS-Like) family has many members such as 17 in Arabidopsis, 16 in rice, 9 in barley (Griffiths et al 2003), 10 in sugarbeet (Chia et al 2008), 11 in Medicago (Wong et al 2014), 26 in soybean (Wu et al 2014) and 23 in cotton (Zhang et al 2015). All of these COL genes are characterized by the presence of three domains namely the B-box 1, B-box 2 and a CCT (CO, COlike, and TOC1) domain (Griffiths et al 2003;Putterill et al 1995;Strayer et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with several other CO-like genes in arabidopsis (COL1 and COL2) (Ledger et al, 2001), pisum sativum (pea) (PsCOLa) (Hecht et al, 2007), and medicago (COLs) (Wong et al, 2014), PpCOL-1 showed a morning phase expression rhythm where its expression peak during morning and fall towards afternoon. This is different than the expression of CO in arabidopsis, which are regulated by light and peaked at the end of the day (Suarez-Lopez et al, 2001).…”
Section: Isolation Of Ppcol-1 and Ppphyb In Pongamiasupporting
confidence: 77%
“…PpCOL-1 showed a morning phase expression rhythm, which is similar to the CO-like in other species under the LD condition; COL1 and COL2 in Arabidopsis (Ledger et al, 2001), PsCOLa in pea (Hecht et al, 2007), and also several other COLs in Medicago (Wong et al, 2014). Their expression levels peak during the morning, then decline during the afternoon.…”
Section: Transcriptional Repressor Cycling Dof Factor (Cdf) (Fornarasupporting
confidence: 59%
See 2 more Smart Citations